Perancangan Sistem Informasi Kelengkapan Resume Medis Pasien Covid-19 - Blessyanica Denison Marchasan; Meira Hidayati; Falaah Abdussalaam (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The goal of this research is to create an information system for filling up medical resumes for Covid-19 patients at RSIA Limijati Bandung. A qualitative research method with a descriptive approach was use in this study. Observation, interviews, and literature review are examples of data collection techniques. The waterfall method is utilize in the software development process. The following issues were discovered as a result of the investigation conducted: (1). Many medical records are returned to the treatment room because to incomplete medical resumes. (2). The process of checking for completeness and generating reports is still done by hand, which means that patient data is retyped into a computer.